Inhibition of fusion of embryonic muscle cells in culture by tunicamycin is prevented by leupeptin (The Rockefeller University Press, 1981)
The carbohydrate requirement for alignment and fusion of embryonic quail muscle cells has been examined in tissue culture by use of tunicamycin (TM). The mononucleated, spindle-shaped proliferating myoblasts were treated with TM at various times before fusion and differentiation into multinucleated muscle fibers capable of spontaneous contraction. Tm blocked protein glycosylation and expression of glycoproteins on the cell surface, and strongly inhibited fusion when added to cultures of differentiating muscle cells before the fusion "burst," but had no apparent effect on cell alignment. The inhibition of fusion was partially prevented when TM was administered in the presence of protease inhibitors such as leupeptin and pepstatin, but the inhibition of glycosylation was not prevented. Both glycosylation and fusion were completely restored to normal by the removal of the antibiotic from the medium. These studies provide strong support for the idea that myoblast fusion is partially mediated by glycoproteins with asparagine-linked oligosaccharides. However, the requirement for the carbohydrate portion of the glycoprotein appears to be indirect in that it acts to stabilize the protein moiety against proteolytic degradation. Our findings do not rule out the possibility that oligosaccharide units of surface glycolipids have some role in myoblast fusion.